Effectiveness of a Third Dose of BNT162b2 mRNA Vaccine. (2nd November 2021) - Saciuk, Yaki; Kertes, Jennifer; Shamir Stein, Naama; Ekka Zohar, Anat
Abstract: A retrospective cohort study was carried out in a large Israeli health maintenance organization to determine vaccine effectiveness (VE) of a third dose of BNT162b2 vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Of nearly 1 million members receiving 2 doses of BNT162b2 in January–February 2021, infection rates (based on polymerase chain reaction results) were compared between those who received a third dose with those who did not during August–October 2021 (maximum, 70 days). Crude VE was 92.9% (95% confidence interval [CI], 92.6%–93.2%) and adjusted VE was 89.1% (95% CI, 87.5%–90.5%). We conclude that the third dose provides added protection against SARS-CoV-2 infection for those vaccinated 6 months ago. Abstract : Providing a third dose of BNT152b2 6 months after the first 2 doses evidenced a vaccine effectiveness against infection rate of 89%. The reduction in infection risk 2 months after the third-dose vaccination campaign reinforces the wisdom of its implementation.